Просування діяльності підприємства малого бізнесу у мережі Інтернет - Вовк, Наталія; Богуш, Христина (Видавництво Львівської політехніки, 2019)
Recently the popularity of social networks has increased, so entrepreneurs do not lose the opportunity to use these platforms to promote their own business. Effective for beauty salons is a social network Instagram, where you can use various tools to promote your business account. Advertising on social networks is convenient because it is possible to instantly get feedback from your clients. It allows you to timely analyze the work done, edit plans, create new posts for effective content every time.
Keywords: соціальна мережа; реклама; Instagram; контент; салон краси